Successful Long-Term Management of Canine Superficial Necrolytic Dermatitis With Amino Acid Infusions and Nutritionally Balanced Home-Made Diet Modification - Jaffey, Jared A.; Backus, Robert C.; Sprinkle, Megan; Ruggiero, Catherine; Ferguson, Sylvia H.; Shumway, Kate (Frontiers in Veterinary Science, 2020)
A 10-year old, castrated male, Bichon Frise with a history of hyperadrenocorticism and intrahepatic portal vein hypoplasia was diagnosed with superficial necrolytic dermatitis (SND). The dog exhibited thick crusts on the chin, muzzle, prepuce, and paws. In addition, the dorsal surfaces of all paws were erythematous while the palmar/plantar surfaces were hyperkeratotic, hardened, and painful. The dog was treated with intravenous amino acid infusions (AAI), raw egg yolks, as well as zinc and omega-3 fatty acid oral supplements. The dog required amino acid infusions once every 2 to 3 weeks because this coincided with recrudescence of painful skin lesions. The dog was subsequently diagnosed with diabetes mellitus. A consult with the Nutrition Service was pursued 220 days after the original SND diagnosis because of concern for feeding raw eggs and for malnutrition since appetite was variable, muscle condition was reduced, and greater than 50% of ingested calories were from foods that were not nutritionally complete. There was also concern regarding the variability of the diet and the impact it would have on the management of diabetes mellitus. The diet was prepared by the dog owner according to a provided recipe and presented twice daily. The diet was rich in high quality protein and fat. All other treatments including medications, supplements, and bathing schedule remained unchanged at the time of diet modification. The dog was subclinical for SND associated clinical signs approximately 3 weeks after the diet modification, which also coincided with the last AAI. The AAI was postponed and was next administered 7 weeks later (i.e., 10 weeks from the previous infusion). The dog remained subclinical for SND related clinical signs and continued to receive AAI once every 10 to 12 weeks until he was euthanized 718 days later for complications related to severe multi-drug resistant, skin infections. In conclusion, this report highlights a novel role for nutritionally balanced home-made diets designed by a board-certified veterinary nutritionist could substantially increase time interval between AAI and outcome in dogs with SND.